In the Footsteps of My Countrymen: Atmospheric Chemistry in New England, Los Angeles, and the Southeast United States - Joost deGouw (Perspectives of Earth and Space Scientists)
Abstract The formation of organic aerosol in the atmosphere degrades air quality and impacts climate change, but has been poorly understood for many years. This article gives a personal history of field studies that have advanced my scientific understanding. Measurements in New England in 2002, Los Angeles in 2010, and the Southeast U.S. in 2013 showed how organic aerosol is formed in these regions, which are distinctly different in their mixtures of natural and anthropogenic emissions. In taking this research path, I followed in the footsteps of two countrymen, Arie Haagen‐Smit and Frits Went, who did foundational work on air pollution in Los Angeles and haze formation from natural emissions.